THE ROLE OF MOBILE HEALTH APPLICATIONS IN MANAGING CHRONIC DISEASES: A SYSTEMATIC REVIEW - Felipe Souza; Pedro Silva; Sakura Suzuki (Journal of World Future Medicine, Health and Nursing, 2026)
Chronic diseases such as diabetes, hypertension, and cardiovascular diseases are leading causes of morbidity and mortality worldwide. The management of these conditions is often complex and requires ongoing monitoring and adherence to treatment plans. Mobile health (mHealth) applications have emerged as a promising tool for improving chronic disease management, providing patients with real-time monitoring, medication reminders, and lifestyle recommendations. This systematic review aims to evaluate the effectiveness of mHealth applications in managing chronic diseases, examining their impact on patient outcomes, engagement, and healthcare costs. A comprehensive search of electronic databases was conducted, and studies assessing the use of mHealth applications for chronic disease management were included. Data were analyzed for clinical outcomes, user satisfaction, and adherence rates. The findings suggest that mHealth applications can significantly improve patient engagement, enhance self-management behaviors, and lead to better health outcomes in chronic disease management. However, the effectiveness varies across different conditions, with more robust evidence for conditions like diabetes and hypertension. Challenges such as data privacy concerns, technology access issues, and patient adherence remain barriers to widespread adoption. In conclusion, mHealth applications have a valuable role in chronic disease management, but further research is needed to optimize their use and address existing challenges.